Exalted redox frameworks of Cu-MOF/polyaniline/RGO based composite electrodes by integrating silver nanoparticles as a catalytic agent for superior energy featured supercapatteries. (20th December 2021) - Roman, Muhammad; Gillani, S.S.A.; Farid, Sidra; Shakil, M.; Ahmad, Riaz; Iqbal, Muhammad Zahir; Faisal, Mian Muhammad; Ahmed, Iqra; Alam, Shahid
Highlights: Redox-active sites enabled solitary-MOFs based catalyzed quaternary composite (copper-MOF/polyaniline/reduced-graphene-oxide/silver nanoparticles) are utilized as a battery-type electrode. Incorporation of noble catalyst AgNPs has greatly accelerated the redox chemistry of copper-MOF/polyaniline/reduced-graphene-oxide ternary composite. The solitary-MOFs based catalyzed quaternary composite electrode (copper-MOF/polyaniline/reduced-graphene-oxide/silver nanoparticles) stand with high specific capacity along with good cyclic stability. Assembled supercapattery system showed excellent energy and power densities of 52 Whkg −1 and 10, 200 Wkg −1, respectively. Abstract: Designing of novel porous materials with multifunctional properties and having versatile nanogeometries called metal organic frameworks (MOFs) that are emerging as a remarkable contender to upsurge the performance of renewable energy storage devices. Here, we widely investigate the hydrothermally synthesized copper-MOF (M1) and its based composites which were made by physical blending technique for high energy density supercapattery device. It includes copper-MOF/polyaniline (M2), copper-MOF/polyaniline/reduced-graphene-oxide (M3) and copper-MOF/polyaniline/reduced-graphene-oxide/silver-nanoparticles (M4). The hydrothermally synthesized copper-MOF exhibits a specific capacity of 14.8 mAh/g while its based composites show 39.8, 52.4 and 118 mAh/g at initial current density of 0.5 A/g in three electrodes electrochemical setup. Owing to excellent electrochemical properties, the composite M4 is utilized for real device fabrication as battery type electrode by conjugating with highly porous carbon electrode separated by cellulose filter paper. This hybrid paradigm endorses promising power density of 1192 W/kg at energy density of 52 Wh/kg, and still holds the energy density of 27.2 Wh/kg by delivering outstanding power density of 10, 200 W/kg. Cyclic durability is tested by exposing the supercapattery to 3000 charge-discharge cycles. As a result, the supercapattery system retains interesting cyclic stability of 91.2% along with faradic efficiency of 99.6%. Overall, this unique architecture of MOFs-based composites would assist to meet the ever-increasing renewable energy demands to power this world. Graphical abstract: Image, graphical abstract